Sienkiewicz w świecie przedmiotów ? osobiste zapiski pisarza o modzie i architekturze = Sienkiewicz in the world of things ? the writer's personal notes on fashion and architecture - Kuniczuk-Trzcinowicz, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The authoress tries to show Sienkiewicz as a person interested in a man and the environment at the aesthetic level. The writer in his correspondence left many traces of organizing his home space: he furnished apartments, brought out the equipment from the trip, which later served as the decoration of his houses. These issues became the subject of Sienkiewicz's postal reports, allowing an analysis his tendencies, habits and aesthetic sensitivity.
Keywords: Sienkiewicz, Henryk (1846-1916); codzienność; korespondencja; rodzina; estetyka; list; everyday consciousness; correspondence; family; aesthetics; letter